Regimes de sentidos em espaços temáticos paulistanos: consumo de móveis e objetos de decoração - Barcelos, Maria Claudia Vidal (2014)
The present study regards São Paulo s city commerce of furniture and decoration objects. We aim to understand and systematize sense production on the context of this segment s consumption from the way intersubjective relations are settled between subjects and thematic spaces. In that way we question how do subjects allow themselves to be seen by the occupation of these thematic spaces and give meaning to sense for Paulistano s decoration commerce? As corpora were taken two thematic streets of the city, RuaTeodoro Sampaio and Alameda Gabriel Monteiro da Silva, on specific sites where concentration of decoration segment stores is bigger. As hypothesis we assume that stores organize themselves in a strategic way, according to the values practiced on the spaces where these stores are placed. These streets are presumed as strong Addressers that will interfere on subjects presence way. As a complement to our investigation we analyze Dunélli House Company, that makes itself seen by three stores on the selected sites. On these thematic spaces occur different sociability ways presentified in their enunciates that make the consumption sense to be, promoting identities and social interaction regimes. The theoretical and referential basis adopted is Discursive Semiotics, from A. J. Greimas legacy, with his proposition concerning sense generative path and narrative grammar. The development of this theory on E. Landowski s Sociossemiotics founds visibility regimes and sense regimes analysis from the kinds of interaction that happen on these spaces, as well as J.M. Floch and A. C. de Oliveira s approach on Plastic Semiotics. The conclusion points that these thematic routes are strong Addressers, able to delineate the kinds of subjects that come to be seen on selected sites and give meaning to sense regarding Paulistano s decoration commerce